2022
DOI: 10.3390/cells11111798
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Microbiome-Gut-Brain-Axis Communication Influences Metabolic Switch-Associated Responses in the Mosquito Anopheles culicifacies

Abstract: The periodic ingestion of a protein-rich blood meal by adult female mosquitoes causes a drastic metabolic change in their innate physiological status, which is referred to as a ‘metabolic switch’. While understanding the neural circuits for host-seeking is modestly attended, how the gut ‘metabolic switch’ modulates brain functions, and resilience to physiological homeostasis, remains unexplored. Here, through a comparative brain RNA-Seq study, we demonstrate that the protein-rich diet induces the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…A blood meal taken by a female mosquito can induce a pronounced metabolic change in its physiological status (Figure 2A). This phenomena is known as a ' metabolic switch' (Das De et al, 2022). Das De et al compared the transcriptome of sugar-fed and blood-fed mosquitos using RNA-seq and showed that feeding blood (a high protein diet), induced expression of transcripts in the brain that are related to mitochondrial function and energy metabolism (Figure 2B) (Das De et al, 2022).…”
Section: Adult Mosquitoesmentioning
confidence: 99%
See 3 more Smart Citations
“…A blood meal taken by a female mosquito can induce a pronounced metabolic change in its physiological status (Figure 2A). This phenomena is known as a ' metabolic switch' (Das De et al, 2022). Das De et al compared the transcriptome of sugar-fed and blood-fed mosquitos using RNA-seq and showed that feeding blood (a high protein diet), induced expression of transcripts in the brain that are related to mitochondrial function and energy metabolism (Figure 2B) (Das De et al, 2022).…”
Section: Adult Mosquitoesmentioning
confidence: 99%
“…This phenomena is known as a ' metabolic switch' (Das De et al, 2022). Das De et al compared the transcriptome of sugar-fed and blood-fed mosquitos using RNA-seq and showed that feeding blood (a high protein diet), induced expression of transcripts in the brain that are related to mitochondrial function and energy metabolism (Figure 2B) (Das De et al, 2022). Blood meals can also serve as an indirect source for lipids.…”
Section: Adult Mosquitoesmentioning
confidence: 99%
See 2 more Smart Citations
“…The brain-gut axis has been well studied in these diseases, and it provides a bidirectional communication system between the central nervous system and the gastrointestinal tract via diverse signaling pathways, including energy metabolism, oxidative stress, mitochondrial function, and neuroinflammation. (Heintz-Buschart et al, 2018;Das De et al, 2022;Giridharan et al, 2022;Terkelsen et al, 2022) Given the similarities in the immune and neurodegenerative factors between glaucoma and Alzheimer's disease and Parkinson's disease, we speculate that microbial communication between the gastrointestinal tract and the eye is involved in the progressive neurodegeneration in glaucoma.…”
Section: Introductionmentioning
confidence: 96%